Evaluation of the Antihyperuricemia Activity of Bajakah Tampala Stem Ethanol Extract (Spatholobus littoralis Hassk.) in Male White Mice (Mus musculus) - Nurul Hidayah; Gabena Indrayani Dalimunthe (NSMRJ: Nusantara Scientific Medical Research Journal, 2022)
Hyperuricemia is elevated blood uric acid. Blood uric acid can harm health. Allopurinol can lower uric acid, but it has harmful side effects. The community has treated various diseases with Bajakah stems. This study examined Bajakah Tampala stem ethanol extract secondary metabolites and antihyperuricemia activity. This research identified the bajakah tampala stem plant (Spatholobus littoralis Hassk.), manufactured simplicia, characterized simplicia, phytochemically screened, prepared the ethanol extract, and tested its antihyperuricemia activity against male white mice (Mus musculus). The simplicia and Bajakah tampala stem ethanol extract contained flavonoids, tannins, steroids/triterpenoids, alkaloids, and saponins. At 400 mg/kgBB (3.88 mg/dl), the bajakah tampala stem ethanol extract reduces uric acid at the 6th hour, similar to allopurinol at 10 mg/kgBB (3.46 mg/dl).